Smart membranes for oil/water emulsions separation: a review - Dansawad, Panchan (2023)
Oily wastewater poses a significant impact on both environments and human societies. Especially, the treatment of oil/water emulsions for separating oil from water is challenging due to the high stability of oil/water emulsions. Smart membranes, known as stimuli-responsive membranes, are one of the emerging technologies that have been paid wide attention for separating oil/water emulsions in recent years. Smart membranes possess the unique features of switchable wettability between hydrophilicity and hydrophobicity after being triggered by external stimuli and have desired anti-fouling properties. This review summarizes the development of smart membranes for oil/water emulsions separation during the past five years (2018 – present). It was found that solvent stimuli-responsive membranes are the most popular type of smart membranes for oil/water emulsions separation. For multi-stimuli-responsive membranes that can respond to more than one stimulus, future research should focus on developing appropriate fabrication strategies to increase the separation and anti-fouling performances of the membranes. Additionally, surface coating, surface grafting, and copolymer blending are the most popular methods for smart membranes fabrication. However, these methods might not be universally applicable to the different types of stimuli-responsive membranes.